Transformacja Sił Zbrojnych RP w okresie przynależności do Sojuszu Północnoatlantyckiego .......... 27 - Wodnicki, Jacek (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
The aim of this text is to analyze transformation of Polish Armed Forces during twenty years of membership in NATO. The starting point for the research is condition of the army during accession to the Pact, which will be compared with state of Polish Army twenty years later. This analysis covers following aspects: size of the army, funds allocated to defence, ability to carry out expeditionary missions and the ability to defend own territory. Additional part of study is analyze an impact of membership on the aspect of professionalization of the army. The importance of this subject is influenced by the fact that NATO is perceived as most important guarantor of Poland’s security. Twenty anniversary of membership in the alliance is an excellent opportunity to assess changes in the Polish Armed Forces.